Jesus Christ message to all nations - Jeffs, Warren, 1955-; Jesus Christ; Fundamentalist Church of Jesus Christ of Latter Day Saints ([Colorado City, Ariz] : [Fundamentalist Church of Jesus Christ of Latter-day Saints], 2013)
A compendium of prophecies attributed to Jesus Christ by Warren S. Jeffs during 2009-2013, principally at Palestine, Texas.
Introduction -- Warning of the Lord Jesus Christ through his servant Warren Jeffs, to the United States of America ; Warning of the Lord Jesus Christ to all nations ; Policies and general principles of the government of Son Ahman in the kingdom of Ahman -- Continued warnings of Son Ahman to the leaders of the nations of the earth -- Thus saith Son Ahman, even your Lord Jesus Christ, my own will to all nations on earth of full power to be fulfilled, unto all knowing I, God, have spoken eternal power upon all nations -- Jesus Christ, Son Ahman, sendeth power-word of warning to all peoples on earth, warning of judgments of full power, to call on all to repent; thus I am just, and of full authority to render judgment on all nations -- Jesus Christ, who is over all, speaketh strong warning of certain holy power of judgments to be upon nation of my holy power of new Jerusalem, also to all nations -- Jehovah, even Jesus Christ, warn all nations to repent; for I cometh ; Jesus Christ giveth own writing to Supreme Court of Appeals -- Jesus Christ holy will to President of United States of America, new word of now need of just order to be of full now labor. Now do so. Amen -- Jesus Christ message of only peace holy power demonstrating to ruler order to make peace in holy way living -- [Section Revelation] 183-202 -- Proclamation: Administration of president Joseph Smith, Jun. ; Administration of president Brigham Young ; Administration of president John Taylor ; Administration of president John W. Woolley ; Administration of president Lorin C. Woolley ; Administration of president John Y. Barlow ; Administration of president Leroy S. Johnson ; Administration of president Rulon Jeffs ; Administration of president Warren S. Jeffs ; Appendix A. Warnings of previous sending to leaders of the nation -- Appendix B. Appendix of my new word of pure power printed in this my proclamation to all peoples on all lands referencing pages to find my word in this publishing -- Appendix C. Documents showing the legal and religious establishing and continuing of the Fundamentalist Church of Jesus Christ of Latter-day Saints among men on earth, thy Lord establishing his church April 6, 1830, through Joseph Smith, continued on earth through my priesthood; now a legal organization according to law of land among men, saith Jesus Christ, your Lord -- Word of the Lord Jesus Christ of continued sacred warning to all peoples on earth -- Second edition continued revealings -- Compiling errors of first edition of now correction.
'President Warren S. Jeffs, Mouthpiece of God ; Jesus Christ, Author'--4th preliminary page.
Keywords: Jeffs, Warren, -- 1955-; Fundamentalist Church of Jesus Christ of Latter Day Saints; Prophecy; Eschatology; Judgment Day; Private revelations; Pedophilia -- Religious aspects